Invention and the life course: Age differences in patenting - Kaltenberg, Mary; Jaffe, Adam B.; Lachman, Margie E. (Research Policy, 2023)
Previous research suggests creative ability peaks at ages between the mid 30s and early 40s, but has not focused on the role of age-related changes in cognitive abilities in this pattern. Cognitive processes show aging-related increases in experience-based knowledge (pragmatics or crystallized abilities) and decreases in the ability to process novel information quickly and efficiently (mechanics or fluid abilities). We explore the role of these age-related changes in the invention process, using a new database created by combining the publicly available patent data with information on inventor ages scraped from directory websites for approximately 1.2 million U.S.-resident inventors patenting between 1976 and 2017. We have made these data publicly available on the Harvard Dataverse and full documentation can be found in Kaltenberg et al. (2021) In the current paper, we present some descriptive statistics, and explore changing patterns of invention as inventor's age. For solo inventors, backward citations and originality increase with age, consistent with their being connected to crystallized intelligence. Forward citations, number of claims, and generality measures, as well as a citation-based measure of disruptiveness decline with inventor age, consistent with a connection to fluid intelligence. A similar pattern was found for performance in teams based on the average age of inventors in the team. Exploration of age diversity showed that teams with a wider age range had patents that are slightly more important (i.e., with more forward citations). Merging of these new data with other data that capture diverse aspects of inventors' environment and incentives offers rich potential for new research on invention.